2023
DOI: 10.2196/37540
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Norovirus in England Using Existing and Emerging Syndromic Data: Infodemiology Study

Abstract: Background Norovirus is associated with approximately 18% of the global burden of gastroenteritis and affects all age groups. There is currently no licensed vaccine or available antiviral treatment. However, well-designed early warning systems and forecasting can guide nonpharmaceutical approaches to norovirus infection prevention and control. Objective This study evaluates the predictive power of existing syndromic surveillance data and emerging data s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Two different meta-analyses were performed: one for the outcome after the first dose and another for the outcome after the second dose. All analyses were performed using the programing language R (19) .…”
Section: Methodsmentioning
confidence: 99%
“…Two different meta-analyses were performed: one for the outcome after the first dose and another for the outcome after the second dose. All analyses were performed using the programing language R (19) .…”
Section: Methodsmentioning
confidence: 99%
“…The 29 studies identified from the full screen included a range of different syndromic surveillance systems from ten countries and territories across Korea, United States, France, Sweden, Netherlands, Spain, Canada, United Kingdom, Japan, and Portugal. Just over half of the studies (52%, 15/29) were reported from the United States and United Kingdom [8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]. About 55% (16/29) [13,16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] of the studies indicated that syndromic surveillance exhibited the potential to detect GI infections earlier than traditional surveillance, while a further 10% (3/29) of studies indicated that syndromic surveillance exhibits the potential to detect GI infections or symptoms at an early stage but with limitations [15,20,36]; a further 3% (1/29) highlighted that syndromic surveillance exhibits potential to detect GI infections or symptoms at an early stage only when combined with traditional surveillance system [18].…”
Section: Summary Of the Syndromic Surveillance Systemsmentioning
confidence: 99%
“…The syndromic surveillance systems reported in the selected studies described different sources of syndromic data, of which the emergency department (ED) setting was the most frequently utilized [12,[15][16][17]19,24,27,33,34,36]. Of the included studies, 3/29 reported the use of multiple or combined syndromic surveillance systems [24,25,27]. The other systems reported in the included studies were National Health Service (NHS) Direct calls (a telehealth system) [13], GP surveillance [26,29,38], integrated medical records from inpatient, outpatient, laboratory, and pharmacy data [18,21,[23][24][25]27,28,35,39], electronic medical records [8,18,23,32], a nurse advice hotline [21], nursing home public health surveillance system [28], internet search queries [30], and nursery school absenteeism [31].…”
Section: Type Of Syndromic Surveillance Systemsmentioning
confidence: 99%